Sustainable valorization of waste plastic into nanostructured materials for environmental, energy, catalytic and biomedical applications: A review - Kapoor A.; Raghunathan M.; Lal B.; Kumar P.; Srivastava N.; Devnani G.L.; Pal D.B. (My University, 2025)
The extensive production and utilization of plastic products are inevitable in the current scenario. However, the non-degradable nature of waste plastic generated after use poses a grave concern. Comprehensive efforts are being made to find viable technological solutions to manage the escalating challenge of waste plastic. This review focuses on the progress made in transformation of waste plastic into value-added nanomaterials. An overview is provided of the waste plastic issue on a global level and its ecological impacts. Currently established methodologies for waste plastic management are examined, along with their limitations. Subsequently, state-of-the-art techniques for converting waste plastic into nanostructured materials are presented, with a critical evaluation of their distinct merits and demerits. Several demonstrated technologies and case studies are discussed regarding the utilization of these nanomaterials in diverse applications, including environmental remediation, energy production and storage, catalytic processes, sensors, drug delivery, bioimaging, regenerative medicine and advanced packaging materials. Moreover, challenges and prospects in the commercial level production of waste plastic-derived nanomaterials and their adoption for industrial and practical usage are highlighted. Overall, this work underscores the potential of transforming waste plastic into nanostructured materials for multifaceted applications. The valorization approach presented here offers an integration of waste plastic management and sustainable nanotechnology. The development of such technologies should pave the way toward a circular economy and the attainment of sustainable development goals. © 2024 Elsevier Ltd